White guard - Bulgakov, Mikhail, 1891-1940 (Yale University Press, 2008)
White Guard, Mikhail Bulgakov's semi-autobiographical first novel, is the story of the Turbin family in Kiev in 1918. Alexei, Elena, and Nikolka Turbin have just lost their mother-their father had died years before-and find themselves plunged into the cha.